1989
DOI: 10.1037/0021-843x.98.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Impact of distressed and aggressive behavior.

Abstract: Two studies examined the hypothesis that distressed behavior induces negative emotions in others but also prompts solicitousness and deters aggression. In Study 1, 48 marital dyads rated various behaviors in terms of their feelings and reactions toward a spouse engaging in each behavior. Distressed behavior prompted both negative and solicitous emotions, but deterred hostile reactions. Aggressive behavior prompted negative feelings and hostile and argumentative reactions. In Study 2, 41 couples rated videotape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 12 publications
(31 reference statements)
3
60
1
Order By: Relevance
“…It is intriguing that this increased reactivity was specific to angry behaviors displayed by fathers. Although both angry and dysphoric behaviors are potentially aversive to others, as noted above, they have somewhat different interpersonal implications and elicit different responses (Biglan et al, 1989). In particular, angry behavior reflects a clear threat signal (Blanchard & Blanchard, 2009), whereas this is not the case for dysphoric behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that this increased reactivity was specific to angry behaviors displayed by fathers. Although both angry and dysphoric behaviors are potentially aversive to others, as noted above, they have somewhat different interpersonal implications and elicit different responses (Biglan et al, 1989). In particular, angry behavior reflects a clear threat signal (Blanchard & Blanchard, 2009), whereas this is not the case for dysphoric behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Biglan, Rothlind, Hops, and Sherman (1989) and Lovejoy and Busch (1993) showed that although distressed behavior elicited mixed affective reactions, it was also likely to elicit supportive behavioral responses. Given the association of such signals with increasing social value over the course of human evolution, we predict that such behavioral responses will have their own reward value.…”
Section: Signaling To Elicit Care and Reduce Threatmentioning
confidence: 93%
“…They found that others find depressive behavior aversive (Biglan et al 1989) and that depressive social behavior is negatively reinforced. Specifically, when depressed women behaved in a depressed manner, other family members were less likely to act aversively (Biglan et al 1985, Hops et al 1987).…”
Section: Prosocial and Coercive Behavior And The Environments That Prmentioning
confidence: 99%